2020
DOI: 10.2147/jaa.s249893
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Asthma Specialist’s Consult Letter: What Do Parents Think About Receiving a Copy?</p>

Abstract: Written summaries about visits with general practitioners' have influenced increased patient knowledge, satisfaction, recollection, and compliance, and strengthened the doctor-patient relationship. All previous studies about this communication pre-dated the electronic medical record (EMR) era, and none examined views from parents of children with asthma. We explored parents' perceptions about receiving a hard copy summary Letter immediately following the visit, with the pediatric asthma specialist about findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Partridge [ 15 ] reported that only 6.8% (9/133) of parents were “seriously upset” by what they read in their copied letters, either because they felt that their parenting was being criticized or because they disagreed with the content. Liapi et al [ 19 ] found only one complaint about content: out of 200 parents, 2 “felt that the letter did not accurately describe what they thought was the cause of the child’s symptoms.” Only 7.8% of the parents surveyed by Amirav et al [ 18 ] said that they felt more anxious after reading their child’s letter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partridge [ 15 ] reported that only 6.8% (9/133) of parents were “seriously upset” by what they read in their copied letters, either because they felt that their parenting was being criticized or because they disagreed with the content. Liapi et al [ 19 ] found only one complaint about content: out of 200 parents, 2 “felt that the letter did not accurately describe what they thought was the cause of the child’s symptoms.” Only 7.8% of the parents surveyed by Amirav et al [ 18 ] said that they felt more anxious after reading their child’s letter.…”
Section: Discussionmentioning
confidence: 99%
“…The body of Copying Letters research repeatedly documents the ways in which parents, as in-home managers of their children’s health, perceive themselves as silent partners of physicians [ 15 - 18 ]. It is clear that these parents valued access to clinician-authored documentation of their child’s care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liapi et al [19] found only one complaint about content: out of 200 parents, 2 "felt that the letter did not accurately describe what they thought was the cause of the child's symptoms." Only 7.8% of the parents surveyed by Amirav et al [18] said that they felt more anxious after reading their child's letter.…”
Section: Principal Findingsmentioning
confidence: 97%
“…The body of Copying Letters research repeatedly documents the ways in which parents, as in-home managers of their children's health, perceive themselves as silent partners of physicians [15][16][17][18]. It is clear that these parents valued access to clinician-authored documentation of their child's care.…”
Section: Pediatric Inpatient Contextmentioning
confidence: 99%